Essence of the Discursive Competence as a Part of Professional Interaction of Future Physicians - Ivanna Vorona (International Society of Philosophy and Cosmology, 2018)
The article is concerned with essence of the foreign language discursive competence of future physicians. All participants of the communication process should know model of verbal and nonverbal behaviour, depending on the circumstances that unfold. When join in communication, for realization of the set communicative goal it is necessary to be able to choose a particular model of verbal behaviour among those models, which already exist, taking into account the communicative situation and the conversation strategy. However, medical students have difficulty connected to the perception and forming of speech messages in in real communicative situations. Furthermore, knowledge of rules and regulations of the foreign language is not in every instance relevant to ways of formation of opinion. Moreover, it is related with in the context of the foreign language learning insufficient level of discursive competence formation. Discursive competence is an important part of the teaching and learning activities. It reflects the nature of cognitive, informational, communicative and reflexive activities and has an impact on the success of communication. Discursive competence of the future physician is the ability of the medical specialist to form, perceive and interpret holistic monologues (messages, presentations, reports, speeches) and dialogic/polylogical (discussions, consideration, conversation, interviews, telephone conversations) oral discourses in a foreign language in accordance with communicative intention within the scope of professionally oriented communication with due consideration of specifics of their pragmatic and grammatical organization, the relationship between extra-linguistic and linguistic factors and the rules of speech etiquette.